(untitled) (Movimenta (ISSN 1984-4298), 2022)
Introduction: The academic environment is marked by numerous factors that generate emotional desordeiras, this reality may have been aggravated by the Covid-19 pandemic. Objective: To verify the prevalence of symptoms of depression and anxiety among physiotherapy students from a Public Institution in Goiás during the COVID-19 pandemic, as well as the factors associated with these symptoms. Methods: Analytical cross-sectional study, carried out with students of the Physiotherapy course at a public university in Goiás. A sociodemographic questionnaire was used to assess life and health habits and sociodemographic profile, to assess symptoms of depression and anxiety, the Beck Depression Inventory (BDI) and the Beck Anxiety Inventory (BAI) were used. Results: 120 questionnaires were analyzed. The median age was 23 years (21.0-23.5) with a predominance of females (85%). The prevalence of moderate to severe symptoms for anxiety and depression was 57.5% and 38.3% respectively. They were associated with emotional symptoms: illness report, medication use, self-report of anxiety and depression, low income, family support, reduced leisure time and physical exercise (p<0.05). Conclusion: A high prevalence of depression and anxiety was found in physical therapy students, the factors associated with anxiety and depression were female sex, having disease, use of anxiolytics and antidepressants and insufficient leisure time. There was an association with anxiety, the use of medication and low income, and with depression not practicing physical activity and family support.